Failed pneumoperitoneum for laparoscopic surgery following autologous Deep Inferior Epigastric Perforator (DIEP) flap breast reconstruction: a case report. Issue 1 (December 2016) - Balkin, Daniel; Duh, Quan-Yang; Kind, Gabriel; Chang, David; McGrath, Mary
Abstract Background Laparoscopic abdominal surgery may prove difficult in patients who have undergone previous abdominal procedures. No reports in the medical literature have presented an aborted laparoscopic procedure for failed pneumoperitoneum following autologous flap-based breast reconstruction. Case presentation A 55-year-old woman presented with recurrent invasive lobular carcinoma of the right breast as well as a history of ductal carcinoma in situ of the left breast. The patient desired to proceed with bilateral skin- and nipple-sparing mastectomies with right axillary lymph node biopsy, followed by immediate bilateral autologous deep inferior epigastric perforator (DIEP) flap-based breast reconstruction. Preoperatively, a computerized tomography angiogram was obtained for reconstructive preparation, which revealed a left adrenal mass. Ensuing work-up diagnosed a pheochromocytoma. Given the concern for breast cancer progression, the patient elected to proceed first with breast cancer surgery and reconstruction prior to addressing the adrenal tumor. Subsequently, 3 months later the patient was brought to the operating room for a laparoscopic left adrenalectomy for the pheochromocytoma. With complete pharmacologic abdominal relaxation, the abdomen proved too tight to accommodate sufficient pneumoperitoneum and the laparoscopy was aborted. The patient was evaluated in the outpatient setting for assessment of abdominal wall compliance at regular intervals. Five months later, the patient was taken back to the operating room where pneumoperitoneum was established without difficulty and the laparoscopic left adrenalectomy was performed without complications. Conclusion Pneumoperitoneum for laparoscopic surgery subsequent to autologous DIEP flap-based breast reconstruction may prove difficult as a result of loss of abdominal wall compliance. Prior to performing laparoscopy in such patients, surgeons should consider the details of the patient's previous reconstructive procedure and assess potential risk factors for difficulty with insufflation. Lastly, careful abdominal examination should be performed to indicate whether laparoscopy for elective procedures should be delayed until abdominal wall compliance normalizes.